Mast Cell Deficiency Protects Mice from Surgery-Induced Neuroinflammation - Xiang Zhang; Hongquan Dong; Fei Wang; Jun Zhang (Mediators of Inflammation)
Neuroinflammation plays a key role in the occurrence and development of neurodegenerative diseases. Microglia, the resident immune cells in the brain, have been recognized to contribute to neuroinflammation. Previous studies have shown that activated mast cells may be involved in surgery-induced neuroinflammation and neuronal apoptosis by using pharmacological methods. This study is aimed at ascertaining the exactly role of mast cells on neuroinflammation with the mast cell-deficient mice. Adult male C57BL6/J wild-type (WT) and mast cell-deficient (C57BL6/J KitWsh/Wsh (Wsh)) mice underwent tibial fracture surgery. Blood-brain barrier (BBB) breakdown, microglial activation, and neuroinflammatory levels were examined at 1 day after surgery. Surgery-induced BBB breakdown, microglial activation, and neuroinflammatory levels were significantly, pharmacologically reduced using a mast cell stabilizer, cromolyn sodium in WT mice (P<0.05). These results were reproduced with mast cell deficiency. WT mice administered intraventricularly with cromolyn exhibited reduced BBB breakdown, microglial activation, and neuroinflammatory levels versus vehicle (P<0.05). But there was no effect of cromolyn versus vehicle in Wsh mice, clarifying the specificity of cromolyn on brain mast cells. These findings demonstrated that activated mast cells promote surgery-induced BBB breakdown and neuroinflammation in mice, and open up a new therapeutic target for neuroinflammation-related diseases.